Bubble dynamics in various commercial sparkling bottled waters. (October 2015) - Liger-Belair, Gérard; Sternenberg, Florine; Brunner, Stéphane; Robillard, Bertrand; Cilindre, Clara
Graphical abstract: Highlights: Observations were made relevant to common situations involving the service of sparkling waters. Bubble dynamics were examined in glasses poured with commercial waters holding different levels of CO2 . Waters clearly differentiate with regard to their bubble dynamics and losses of CO2 . Results are discussed through mass transfer considerations, including molecular diffusion, and gas solution thermodynamics. Abstract: Observations were made relevant to common situations involving the service of various sparkling waters. Bubble dynamics and progressive losses of dissolved CO2 were closely examined in three various batches of carbonated waters holding different levels of CO2 . During the turbulences of the pouring process, a cloud of bubbles appears in the water bulk. Under the action of buoyancy, bubbles progressively reach the free surface, and the cloud of bubbles finally vanishes. Bubbles also nucleate on the glass wall, where they grow by diffusion until buoyancy forces them to detach and rise to the free surface to release their CO2 . The three batches of sparkling waters were clearly differentiated with regard to their bubbles dynamics and losses of dissolved CO2 . Our observations were systematically rationalized and discussed on the basis of mass transfer considerations including molecular diffusion, basic concepts of gas solution thermodynamic equilibrium, and bubble dynamics.